(untitled) (Journal of Medicine, 2008)
Visceral leishmaniasis (Kala-azar) is endemic in many countries including Bangladesh. Clinical presentation of visceral leishmaniasis in children and adult may vary and at time may simulate many tropical and hepatobilliary diseases. Jaundice and ascites is not common in some patients. In this series of eleven cases Jaundice, splenomegaly, hepatomegaly and ascites are present in 55%, 100%, 91%, 27% of cases respectively. So, Kala-azar should be kept in mind while dealing with cases of many such clinical findings. Â DOI = 10.3329/jom.v8i1.1374 J MEDICINE 2007; 8 : 14-16